TRADISI KRITIK TAFSIR: Diskursus Kritisisme Penafsiran dalam Wacana Qur’anic Studies - MK. Ridwan (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2017)
Abstract: This paper aims to discuss the methodology of interpretation criticism in the qur'anic studies discourse. As new plots in the Qur'an studies, the interpretation criticism has not been much sought after by Qur’anic scholars. As a consequence, in methodological discourse has not yet found a definite method can be used to criticize an interpretation. As for the thought-provoking critique of the interpretation for this still are sporadic and likely are political-ideological. For that, it needs special attention in developing area studies the Quran towards the study criticism of interpretation. Finally, this paper gives the conclusion that, in the discourse of criticism the methodological framework needed interpretation, as a step towards the operational interpretation of criticism. So, the criticism was done not nuanced political-ideological, but able to uphold the values of objectivity, comprehensiveness, scientific and systematic. There are at least four operational steps in carrying out work interpretation of criticism of the region of ontology, epistemology, and axiology i.e; Firstly, the critic must understand the substance of exegesis are an interpretation as process and interpretation as a product. Secondly, understand the construction of criticism interpretation, namely the construction of the historicity of the critique, the base of criticism, the purpose of criticism, as well as the principles and parameters of criticism. Thirdly, start working with two regions exegesis critique work i.e; intrinsic and extrinsic criticism. Fourthly, give the evaluation and assessment of the object of study of criticism that is good and decent, or perverted and unworthy of being used.Abstrak: Tulisan ini bertujuan untuk mendiskusikan metodologi kritik tafsir dalam diskursus wacana Qur’anic Studies. Sebagai wilayah garapan baru dalam studi al-Qur’an, kritik tafsir belum banyak diminati oleh kalangan sarjana al-Qur’an. Akibatnya, dalam wacana metodologis belum banyak ditemukan metodebaku yang dapat digunakan untuk mengkritisi sebuah tafsir. Adapun pemikiran kritik tafsir selama ini masih bersifat sporadis dan cenderung bersifat politis-ideologis. Untuk itulah dibutuhkan perhatian khusus dalam mengembangkan wilayah studi al-Qur’an ke arah studi kritik tafsir. Akhirnya, tulisan ini memberikan kesimpulan bahwa, dalam diskursus kritisisme penafsiran, dibutuhkan kerangka metodologis sebagai langkah operasional kritik tafsir. Sehingga, kritik yang dilakukan tidak bernuansa politis-ideologis, namun mampu mengedepankan nilai-nilai objektivitas, komprehensivitas, ilmiah dan sistematis. Setidaknya terdapat empat langkah operasional dalam melaksanakan kerja kritik tafsir yang bermuara pada wilayah ontologis, epistemologis, dan aksiologis yaitu; Pertama, kritikus harus terlebih dahulu memahami hakikat tafsir yakni tafsir sebagai proses (interpretation as process) dan tafsir sebagai produk (interpretation as product). Kedua, memahami konstruksi kritik tafsir, yaitu historisitas kritik, landasan kritik, tujuan kritik, serta prinsip dan parameter kritik. Ketiga, memulai kerja kritik tafsir dengan dua wilayah kerja yaitu; kritik intrinsik dan kritik ekstrinsik. Keempat, memberikan evaluasi dan penilaian terhadap objek kajian kritik yaitu, baik (maḥmūd) dan layak pakai (maqbūl), atau menyeleweng (munḥarif) dan tidak layak digunakan (mardūd).